Bilingual performance on nonword repetition in Spanish and English - Summers, Connie (Int J Lang Commun Disord, 2010)
BACKGROUND: Nonword repetition (NWR) involves the ability to perceive, store, recall and reproduce phonological sequences. These same abilities play a role in word and morpheme learning. Cross-linguistic studies of performance on NWR tasks, word learning, and morpheme learning yield patterns of increased performance on all three tasks as a function of age and language experience. These results are consistent with the idea that there may be universal information-processing mechanisms supporting language learning. Because bilingual children’s language experience is divided across two languages, studying performance in two languages on NWR could inform one’s understanding of the relationship between information processing and language learning. AIMS: The primary aims of this study were to compare bilingual language learners’ recall of Spanish-like and English-like items on NWR tasks and to assess the relationships between performance on NWR, semantics, and morphology tasks. METHODS & PROCEDURES: Sixty-two Hispanic children exposed to English and Spanish were recruited from schools in central Texas, USA. Their parents reported on the children’s input and output in both languages. The children completed NWR tasks and short tests of semantics and morphosyntax in both languages. Mixed-model analysis of variance was used to explore direct effects and interactions between the variables of nonword length, language experience, language outcome measures, and cumulative exposure on NWR performance. OUTCOMES & RESULTS: Children produced the Spanish-like nonwords more accurately than the English-like nonwords. NWR performance was significantly correlated to cumulative language experience in both English and Spanish. There were also significant correlations between NWR and morphosyntax but not semantics. CONCLUSIONS & IMPLICATIONS: Language knowledge appears to play a role in the task of NWR. The relationship between performance on morphosyntax and NWR tasks indicates children rely on similar language-learning mechanisms to mediate these tasks. More exposure to Spanish may increase abilities to repeat longer nonwords. This knowledge may shift across levels of bilingualism. Further research is needed to understand this relationship, as it is likely to have implications for language teaching or intervention for children with language impairments.